High sensitivity cardiac troponin and the under-diagnosis of myocardial infarction in women: prospective cohort study. (21st January 2015) - Shah, Anoop S V; Griffiths, Megan; Lee, Kuan Ken; McAllister, David A; Hunter, Amanda L; Ferry, Amy V; Cruikshank, Anne; Reid, Alan; Stoddart, Mary; Strachan, Fiona; Walker, Simon; Collinson, Paul O; et al.
Abstract : Objective To evaluate the diagnosis of myocardial infarction using a high sensitivity troponin I assay and sex specific diagnostic thresholds in men and women with suspected acute coronary syndrome. Design Prospective cohort study. Setting Regional cardiac centre, United Kingdom. Participants Consecutive patients with suspected acute coronary syndrome (n=1126, 46% women). Two cardiologists independently adjudicated the diagnosis of myocardial infarction by using a high sensitivity troponin I assay with sex specific diagnostic thresholds (men 34 ng/L, women 16 ng/L) and compared with current practice where a contemporary assay (50 ng/L, single threshold) was used to guide care. Main outcome measure Diagnosis of myocardial infarction. Results The high sensitivity troponin I assay noticeably increased the diagnosis of myocardial infarction in women (from 11% to 22%; P<0.001) but had a minimal effect in men (from 19% to 21%, P=0.002). Women were less likely than men to be referred to a cardiologist or undergo coronary revascularisation (P<0.05 for both). At 12 months, women with undisclosed increases in troponin concentration (17-49 ng/L) and those with myocardial infarction (≥50 ng/L) had the highest rate of death or reinfarction compared with women without (≤16 ng/L) myocardial infarction (25%, 24%, and 4%, respectively; P<0.001). Conclusions Although having little effect in men, a high sensitivity troponin assay with sex specific diagnostic thresholds may double the diagnosis of myocardial infarction in women and identify those at high risk of reinfarction and death. Whether use of sex specific diagnostic thresholds will improve outcomes and tackle inequalities in the treatment of women with suspected acute coronary syndrome requires urgent attention.